PENINGKATAN KINERJA DENGAN MELAKUKAN ANALISIS PERANCANGAN MENGGUNAKAN PENDEKATAN BALANCED SCORECARD PADA RSUD DI WILAYAH INDONESIA TIMUR (STUDI KASUS PADA RSUD DR.T.C.HILLERS MAUMERE) - Oktaviana Florida Jelalu (Journal of Management Small and Medium Enterprises (SMEs), 2023)
The purpose of this research is to design the performance measurement by using the Balanced Scorecard approach at Dr.T.C.Hillers Maumere Hospital. A balanced scorecard helps the hospital achieve strategic targets from four perspectives: internally and externally. The methods that are used in collecting the data are observation, interview, and documentation. Based on the discussion result on four indicators of the Balanced Scorecard at Dr.T.C.Hillers Maumere Hospital shows the result of customer perspective which needs to be measured to increase patient satisfaction and loyalty, the financial perspective needs indicator to raise service revenue and cost control (streamline costs) so it can reach independent finance, internal business process perspective needs measurement to increase service innovation, measurement to increase basis service quality and reference, measurement to increase efficiency and effectiveness of service provision procedure and measurement to increase assets management, and then on growth and learning perspective by doing measurement to increase network technology utilization and quality human resources. Thus, it can be concluded that using the Balanced Scorecard as a performance measuring tool could help the hospital attain long-term success in a competitive market situation. Keywords: Performance Measurement; Strategic Target; Balanced Scorecard; Regional Public Hospital